2018
DOI: 10.1007/s00167-018-4965-8
|View full text |Cite
|
Sign up to set email alerts
|

Patella alta and patellar subluxation might lead to early failure with inlay patello-femoral joint arthroplasty

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
1
19
0
3
Order By: Relevance
“…Therefore, patella alta cannot be compensated by this specific implant. This problem has also been observed in another study by Beckmann et al [2]. In their series of 20 patients treated with the HemiCAP® Wave prosthesis, 11 patients underwent revision surgery for recurrent pain and "clunk" phenomenon.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Therefore, patella alta cannot be compensated by this specific implant. This problem has also been observed in another study by Beckmann et al [2]. In their series of 20 patients treated with the HemiCAP® Wave prosthesis, 11 patients underwent revision surgery for recurrent pain and "clunk" phenomenon.…”
Section: Discussionsupporting
confidence: 61%
“…All patients were revised using an onlay-type prosthesis and pain as well as function improved postoperatively. The authors, therefore, concluded that inlay PFA should be considered contraindicated in patients with patella alta and that an onlay PFA system reaching further proximal should be considered [2]. It must be noted, however, that it remains unknown to what extend a larger implant can compensate for patella alta.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies from 2019, concerning the same inlay implant, obtained controversial results. While one showed promising results with a survival rate of 91% at 2 years and 83% at 5 years [ 55 ], the other found a high failure rate of these inlay prostheses [ 56 ]. Many patients had to be revised after 28 months and converted into an onlay prosthesis because of persistent pain and clunck phenomenon.…”
Section: Resultsmentioning
confidence: 99%